Particle beam therapy for nasopharyngeal cancer: A systematic review and meta-analysis. (November 2022) - Ng, Wai Tong; But, Barton; Wong, Charlene H.L.; Choi, Cheuk-Wai; Chua, Melvin L.K.; Blanchard, Pierre; Lee, Anne W.M.
Highlights: Particle beam therapy yields excellent short-term treatment outcomes among NPC patients. Particle beam therapy is generally safe in primary and recurrent NPC patients, with ≥G3 late toxicity rates of 20 % or less. An approximately 5% mortality rate was reported among recurrent NPC patients. Abstract: Background/purpose: A systematic review and meta-analysis were performed to better understand the benefits of particle beam therapy for nasopharyngeal cancer (NPC) treatment. The survival outcomes and toxicity of primary and recurrent NPC patients treated with proton or carbon ion beam therapy were investigated. Method: PubMed, Scopus, and Embase were searched between 1 January 2007 to 3 November 2021. The inclusion and exclusion criteria included studies with either primary or recurrent NPC patients, sample size of ≥10 patients, and proton or carbon ion beam therapy as interventions. Twenty-six eligible studies with a total of 1502 patients were included. We used a random-effect meta-analysis to examine the impact of particle beam therapy on primary NPC patients and qualitatively described the results among recurrent patients. The primary outcome was overall survival (OS), while secondary outcomes included progression-free survival (PFS), local control (LC) and toxicity. Results: The pooled OS at 1-year, 2-year and 3-year and 5-year for primary NPC patients who received particle beam therapy were 96 % (95 % confidence interval (CI) = 92 %-98 %), 93 % (95 % CI = 83 %-97 %), 90 % (95 % CI = 73 %-97 %) and 73 % (95 % CI = 52 %-87 %) respectively. The pooled 1-year and 2-year PFS, and LC for these patients were above 90 %. For locally recurrent NPC patients, the 1-year OS rate ranged from 65 % to 92 %, while the 1-year LC rate ranged from 80 % to 88 %. Both proton and carbon ion beam therapy were generally safe among primary and recurrent patients, with ≥G3 late toxicity rates of 20 % or less. Approximately a 5 % mortality rate was reported among recurrent patients. Conclusions: This systematic review and meta-analysis demonstrated particle beam therapy has great potential in treating NPC, yielding excellent survival outcomes with low toxicity. However, further investigations are needed to assess the long-term outcomes and cost-effectiveness of this newer form of radiotherapy.